Effects of medializing calcaneal osteotomy associated with posterior tibial tendon re-tensioning in flexible flatfoot treatment in adolescents - Barison, Marcio Silva; Oliveira, Rullya Marson De Melo; Parreira, Marcos Gregory Cintra; Prates, Rafael Cardoso; Souza Filho, Lamartine Barbosa de; Cavallari, Gustavo; Figueiredo, Márcio Gomes; Ignácio, Helencar (Journal of the Foot & Ankle, 2024)
Objective: Evaluate the correction of the talonavicular coverage incongruency angles after medializing calcaneal osteotomy associated with talonavicular capsuloplasty and posterior tibial tendon re-tensioning in 12 patients (14 feet) aged between 13 and 16 years. Methods: A retrospective study, using medical records, analyzed radiographs inthe anteroposterior incidence pre- and postoperative after six weeks of surgery. Patients submitted to the medializing calcaneal osteotomy associated with talonavicular capsuloplasty and posterior tibial tendon re tensioning were included. Results: The preoperative talonavicular coverage angle ranged from 15.49 degrees to 31.00 degrees with a mean of 26.02 degrees, and in the postoperative, after six weeks, there was a change in the talonavicular coverage angle ranging from 0.65 degrees to 10.69 degrees, with a mean of 05.56 degrees. In our evaluation, the p-values were < 0.0001, considered extremely significant. The talonavicular incongruency angle in the preoperative ranged from 35.00 degrees to 87.00 degrees, with a mean of 64.00 degrees, and in the postoperative ranged from 0.50 degrees to 19.80 degrees, with a mean of 8.65 degrees. In our evaluation, p-values were <0.0001, considered statistically significant. Conclusion: The results demonstrated statistically significant improvements in the correction of the talonavicular coverage and incongruency angles following medializing calcaneal osteotomy, associated with talonavicular capsuloplasty and posterior tibial tendon re-tensioning, in adolescents with symptomatic flexible flatfoot. Level of evidence II; Prognostic studies - investigating the effect of a patient characteristic on the outcome of disease; Retrospective study